Research on the Path of Shaping the International Image of the Communist Party of China - Sun, Yuewei; Fan, Xiying; Zhao, Xueting; Zhao, Yahan; Cheng, Wenyang (International Journal of Social Sciences and Public Administration, 2024)
With China’s rise in the international arena, shaping the image of political parties has become a focus of international attention.How to tell the story of theCPC to the world and gain recognition and learn from China’s governance experience is a crucial part of China’s internationalisation process.Although "the image and prestige of the party directly affects the destiny of the party, the state, the people and the nation", the CCP still has deficiencies in shaping and spreading its international image.Based on the historical experience, we should focus on the international image shaping countermeasures of the CPC since the 18th National Congress in the aspects of "party construction, value export, diplomatic practice communication, media communication methods, and object demand", in order to enhance its influence and appeal, so that the outside world can better understand, recognize and follow the CPC.